THE CORRELATION BETWEEN THE FAMILY SUPPORT WITH ADHERENCE TO A LOW-SALT DIET IN PEOPLE WITH HYPERTENSION AT WAY PANJI PUBLIC HEALTH CENTER IN 2022 - Sonia, Ni Wayan Soniawati; Simamora, Rotua Suriany; Pelawi, Arabta M. Peraten (Rena Cipta Mandiri, 2023)
Hypertension is one of the non-communicable diseases that is the most important health problem in Indonesia because of its high prevalence. Management of hypertension can be done by undergoing adherence to a low-salt diet. One of the factors that influence the success of a low-salt diet is the presence of family support. This study aims to determine the family support with adherence to a low-salt diet in people with hypertension at Way Panji Public Health Center, in 2022. The research method used is quantitative with cross-sectional analytic research. The population in this study were people with hypertension 20-70 years old at Way Panji Public Health Center totaling 90 people. The data collection technique used type of simple random sampling based on the inclusion criteria and obtained the number of samples as many as 73 respondents. The results showed that with a significant level of 95% or α value of 5% (0,05) the results of the Chi Square obtained p-value (0,000) < α (0,05). This show that H0 is rejected. The conclusion of the study is a the family support with adherence to a low-salt diet in people with hypertension at Way Panji Public Health Center in 2022.